Familial and socio-environmental predictors of overweight and obesity among primary school children in Selangor and Kuala Lumpur. - Tung , Serene E. H.; Shohaimi, Shamarina; Mohd Taib, Mohd Nasir (Nutrition Society of Malaysia, 2011)
Introduction: A cross-sectional study was conducted to determine the familial and socio-environmental predictors of overweight and obesity among 1430, 9-12 year-old primary school children and their parents in Selangor and Kuala Lumpur. Methodology: Body weight and height were measured and body mass index was calculated. Modified Child Feeding (CFQ) and Determinants of Adolescent Social Well-being and Health (DASH) questionnaires were used to measure familial and socio-environmental factors. Results: A total of 17.9% of the children were overweight while 16.0% were obese. Positive relationships were found between child’s BMI and parent’s BMI (r = 0.129, p < 0.01), concern about child’s weight (r = 0.125, p < 0.01) and restriction (r = 0.057, p < 0.05) to unhealthy foods. However, negative relationships were found between child’s BMI with pressure to eat (r = -0.135, p < 0.01) and neighbourhood safety perception (r = -0.053, p < 0.05). The logistic regression analysis showed that being male (Exp(β) = 0.538; 95% CI = 0.421-0.687), higher parent’s BMI (Exp (β) = 1.055; 95% CI = 1.028-1.082), higher concern about child’s weight (Exp (β) = 1.082; 95% CI = 1.030-1.127), low pressure to eat (Exp (β) = 0.857; 95% CI = 0.801-0.916) and low perception of neighbourhood safety (Exp (β) = 0.951; 95% CI = 0.913-0.990) were significantly associated with increased risk of overweight. Conclusion: Parents should be the main target for education to modify children’s weight status. Further research should be carried out to understand the mechanism of influence of parents and the socio-environment on child’s health.